Analyzing the Potential of Artificial Intelligence (AI) in Personalizing Learning to Foster Creativity in Students - Rita Hasibuan; Andina Azizah (Enigma in Education, 2023)
Artificial intelligence (AI) has the capacity to greatly revolutionize education by generating personalized and immersive learning experiences that foster innovation. AI facilitates the customization of education, allowing for the adjustment of instructional techniques and educational resources to cater to the distinct requirements and capabilities of each learner. A literature search was done using several databases, such as PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to look into how artificial intelligence (AI) could be used to personalize learning and encourage creativity in individuals. The utilization of artificial intelligence (AI) in customizing learning holds immense potential for fostering innovative individuals in the field of education. AI helps people be creative in many ways, such as by finding out what interests and skills each person has and then giving them access to the right resources and creating personalized learning experiences. Furthermore, it fosters innovative cooperation among students who share common interests. AI enhances the relevance of learning by prioritizing students' needs and fostering the development of creativity. Students have a high level of involvement and enthusiasm and are afforded additional opportunities for exploration and innovative thought. Nevertheless, it is crucial to maintain a harmonious equilibrium between the influence of technology and the significance of teachers, who continue to be essential in offering direction and motivation to pupils.